Comparison of Three-Dimensional Accuracy of Digital and Conventional Implant Impressions: Effect of Interimplant Distance in an Edentulous Arch - Tan, Ming Yi (QUINTESSENCE PUBLISHING CO INC, 2024)
10.11607/jomi.6855